King of Taos - Evans, Max (Albuquerque, NM University of New Mexico Press, 2020)
The underground world of con men, winos, prostitutes, laborers, and artists has been an abundant source of material for great writers from Dickens to Bukowski. The underground world of Taos, New Mexico, is no different. In the late 1950s this mountain town was higher, brighter, poorer, and farther removed than London, Paris, or Los Angeles, but it was every bit as rich for the explorations of a young writer. Max Evans, the beloved New Mexican writer of such enduring classics of Western fiction as The Rounders and The Hi-Lo Country, returns to form with The King of Taos. Set in the late 1950s, the novel tells the stories of sharp-witted Zacharias Chacon, aspiring artist Shaw Spencer, and a circle of characters who drink, fight, love, argue, and--mostly--talk. Readers will enjoy this witty and moving evocation of unforgettable characters as they look for work, love, comfort, dignity, and bottomless oblivion.
108125
Keywords: Social life and customs -- 20th century; Picaresque fiction; Historical fiction; Taos (N.M.)